PENGARUH PENDIDIKAN KARAKTER TERHADAP PENCAPAIAN HASIL BELAJAR SISWA PADA MATA PELAJARAN AKIDAH AKHLAK DI MI IHYAUL ISLAM PROBOLINGGO - Khofifatus Sholihah; Muhammad Sulistiono; Lia Nur Atiqoh Bela Dina (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2022)
This thesis is aresearch process regarding the influence of character education on student learning outcomes in the subjects of aqidah and morality. The research process was carried out a MI Ihyaul Islam Probolinggo. This research uses quantitative research methods with survey methodologies. So quantitative researchwith the type of survey research method is research to find information about research problems using research instruments and using samples / population to produce research data. The result of the study prove that there is an influence of character education on the achievement of student learning outcomes in the subject of faith morals at MI Ihyaul Islam Probolinggo. The result of this study can be refined by the results of the T hypothesis test, namely the number of T count > T table / 3,796 > 1,671. So if T count > T table then, the variable (x) of character education has an effect on the variable (y). Keywords : methodology, achievement, information, influence, instrument